Legal Protection for Users of The Alodokter Application in Autodebet Cases Without User Consent - Fauzi Purnama, Fahreza; Sutrisno (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2023)
This study aims to identify legal protection as well as legal remedies for consumers who use the Alodokter application for autodebit based on Law no. 8 of 1999 concerning Consumer Protection. The research method is normative, with a statutory approach.The results of the study show that legal protection for users of the Alodokter application is the obligation for business actors toprovide compensation for damage to goods that harm consumers, which can be in the form of refunds or replacement of goods with the same or equivalent value, or health care, and/or compensation. Compensation is made within 7 (seven) days after the transaction date. Legal remedies that can be taken by consumers whose accounts are affectedauto debtwithout approval, namely by peacefully resolving disputes through the process of canceling Alodokter users, resolving disputes through institutions or consumer dispute resolution, up to court.